2016
DOI: 10.7752/jpes.2016.01016
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The aim of this study was to examine the short-term effect of squat exercises performed with an elastic band on static and dynamic squat and vertical jumps in pre-adolescents. A total of 21 children were included as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
10

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 22 publications
(32 reference statements)
0
4
0
10
Order By: Relevance
“…Most likely, the stimulus provided by the bodyweight exercises was not enough or the exercise was too difficult to adapt to each subject (Faingenbaum, 2000), while the elastic band resistance could be easily adapated, thus providing a proper stimulus for the neuromuscular improvements (Ignjatović, Stanković, Radovanović, Marković & Cvećka, 2009). Studies of Lubans, Aguiar & Callister (2010) and Sahin, Aslan & Demir (2016) found improvements in strength similar or higher to free weights training. For body composition, Lubans, Aguiar & Callister (2010) found changes in the percentage of fat-free and fat mass in both sexes, although the bodyweight training group achieved greater results than the elastic resistance group.…”
Section: Effects Of Training With Elastic Bands In Youthsmentioning
confidence: 90%
See 3 more Smart Citations
“…Most likely, the stimulus provided by the bodyweight exercises was not enough or the exercise was too difficult to adapt to each subject (Faingenbaum, 2000), while the elastic band resistance could be easily adapated, thus providing a proper stimulus for the neuromuscular improvements (Ignjatović, Stanković, Radovanović, Marković & Cvećka, 2009). Studies of Lubans, Aguiar & Callister (2010) and Sahin, Aslan & Demir (2016) found improvements in strength similar or higher to free weights training. For body composition, Lubans, Aguiar & Callister (2010) found changes in the percentage of fat-free and fat mass in both sexes, although the bodyweight training group achieved greater results than the elastic resistance group.…”
Section: Effects Of Training With Elastic Bands In Youthsmentioning
confidence: 90%
“…Only 3 studies examined elastic resistance training in subjects less than 18 years old (Coskun & Sahin, 2014;Lubans, Aguiar & Callister, 2010;Sahin, Aslan & Demir, 2016). These studies used 2 weekly sessions and included a total of 159 subjects: 65 used elastic bands, 37 free weights and 22 used their own body weight.…”
Section: Characteristics Of the Studies In Youthsmentioning
confidence: 99%
See 2 more Smart Citations
“…Las edades de los participantes se diferencian en dos grandes grupos. Los estudios realizados en niños abarcan edades comprendidas entre 7 y 12 años (Coskun & Sahin, 2014;Kordi, et al, 2016;Özsu, 2018;ªahin, et al, 2016). Las edades de los sujetos adolescentes se encuentra entre 14 y 19 años (Aloui, et al, 2018;Batalha, et al, 2015;Hammami, et al, 2021;Lubans, et al, 2010).…”
Section: Características De Los Estudiosunclassified